Study on the structure of Fe/MgO catalysts for H2S wet oxidation - Jung, KD; Joo, OS; Kim, CS (KLUWER ACADEMIC/PLENUM PUBL, 2002)
Wet catalytic oxidation was performed at room temperature with 1 wt% Fe/MgO, 4 wt% Fe/MgO, 6 wt% Fe/MgO, 15 wt%/MgO and 30 wt% Fe/MgO catalysts. The 6 wt% Fe/MgO catalyst has a maximum capacity of 2.6 g H2S/g(cat) for H2S removal. The amounts of paramagnetic Fe3+ cations are correlated with the H2D removal capacity of the Fe/MgO catalysts from Mossbauer experiments. It is observed that the deactivation of the 6 wt% Fe/MgO catalyst can be due to the loss of the paramagnetic Fe3+ cations during the reaction.